Cardiovascular determinants of exercise capacity in the Paralympic athlete with spinal cord injury - Theisen, D. (Experimental Physiology, 2012)
This report briefly summarizes the cardiovascular factors that influence exercise physiology and, eventually, sports performance of athletes with a spinal cord injury (SCI). The consequences of an SCI are numerous and concern voluntary muscle function, deep and superficial sensitivity, and autonomic function to a degree determined by the level and completeness of the spinal lesion. Athletes with SCI perform with their upper body, which limits their maximal exercise capacity and puts them at a disadvantage compared with leg exercise in terms of mechanical efficiency and physiological adaptations to exercise. Studies generally find that maximal oxygen consumption and mechanical power output are inversely related to spinal lesion level. Athletes with cervical or dorsal lesions down to Th6 have limited maximal heart rates owing to a lack of sympathetic drive to the heart. Blood redistribution from body areas lacking autonomic control is impaired, thus reducing venous return and limiting cardiac stroke volume during exercise. Thermoregulatory function is affected through a lack of afferent neural feedback and limited efferent vasomotor and sudomotor control below the lesion. Strategies to support venous return and to promote body cooling potentially improve physiological responses and athletic performance, especially in individuals with high lesion levels. The latter are subject to autonomic dysreflexia, a generalized sympathetic vasoconstriction below the lesion resulting from nociceptive stimulations in insensate body regions. Acute episodes induce high blood pressure, may enhance exercise performance and must be treated as a clinical emergency. Deliberate triggering of this reflex is prohibited by the International Paralympic Committee.